A novel design for microfluidic chamber based on reverse flow optimization. Issue 8 (6th November 2017) - Chen, Xueye; Li, Tiechuan
Abstract : Purpose: This paper aims presents topology optimization of microfluidic channels with reverse flow. Design/methodology/approach: A circular chamber with an inlet and an outlet are chosen as an initial design domain. The energy dissipation is chosen as an objective function. The incompressible Navier–Stokes equation is applied for simulating the fluidic motion in channels. An artificial friction force which is proportional to the flow velocity is substituted into the Navier–Stokes equation for controlling the design variable. Findings: The effect of a bifurcation angle between the inlet and the outlet on a topological structure is analyzed. The flow velocity, pressure and design variable for every bifurcation angle are obtained. Originality/value: This work is instructive to the design of a microfluidic system.